WORKING GROUP OF THE YOUNG CARDIOLOGISTS HAS BEEN ESTABLISHED AT THE SOCIETY OF CARDIOLOGY OF THE RUSSIAN FEDERATION (Рациональная фармакотерапия в кардиологии, 2016)
Working group of the Young Cardiologists has been established at the Society of Cardiology of the Russian Federation.